The relationship between ethnocentrism and cultural intelligence. (May 2017) - Young, Cheri A.; Haffejee, Badiah; Corsun, David L.
Abstract: The business world is becoming more diverse and complex with the increase of legally-admitted refugees and immigrants in countries across the globe. The need for culturally-intelligent managers may be more pressing than ever. At the same time, ethnocentrism corresponding to the refugee crisis and mass migration appears to be on the rise. Yet, little is known about the effect of ethnocentrism on diversified working relationships and effective means of reducing ethnocentrism such that it does not impede the successful management of an emerging diverse workforce. Can one be ethnocentric and yet culturally intelligent at the same time? This study examined the relationship between these two constructs in general and the role of cultural intelligence (CQ) as a predictor of ethnocentrism, specifically. The data used to examine the CQ–ethnocentrism relationship was part of an ongoing study examining the efficacy of an experiential training program involving diversified mentoring relationships. In these relationships, primarily white, affluent, university students studying business were assigned to mentor refugees from diverse backgrounds being resettled in the U.S. Using a quasi-experimental design, we found that while ethnocentrism increased for the treatment group, it did not rise as much as it did in the control group, indicating a buffering effect for the diversified mentoring training intervention. Additionally, a negative relationship was found between CQ and ethnocentrism, with CQ predicting ethnocentrism. Discussion focuses on effectiveness of training interventions for increasing CQ and lowering ethnocentrism, and the need for consensus in conceptualization and operationalization of ethnocentrism.